Strengthening Religious Moderation Literacy Through The Snakes And Ladders Game Of Grade 4 Students Of MI Tarbiyatul Athfal Bululor Jambon - Aisyah Putri; Fida Antika; Ilfa Nurrohmatin; Pipin Tri Avita Sari; Mambaul Ngadhimah; Dewi Susilo Reni; Erly Rizki Kamalia; Romi Hamfrisa Putra (Institut Agama Islam Negeri Ponorogo, 2025)
Strengthening religious moderation literacy from an early age is crucial in the context of Indonesia's multicultural and religious society to prevent intolerant and extreme attitudes. This article aims to describe efforts to strengthen religious moderation literacy in fourth-grade students at MI Tarbiyatul Athfal Bululor, Jambon, Ponorogo through the Giant Snakes and Ladders game. This activity was implemented within the Community Service Lecture (KPM) program using the Asset-Based Community Development (ABCD) approach, which includes the stages of discovery, dream, design, define, and destiny. The implementation method was carried out through observation, socialization, material delivery, educational games, and evaluation. The results of the activity showed that the use of the Snakes and Ladders game as a learning evaluation medium was able to improve students' understanding and literacy of the values ​​of religious moderation, as demonstrated by the ability to answer questions quickly and accurately and increased enthusiasm for learning. In addition, this medium was considered effective and interesting as an alternative learning evaluation at the elementary school level. In conclusion, the Giant Snakes and Ladders game can be an innovative and effective learning medium in strengthening religious moderation literacy in elementary school students